2020
DOI: 10.1080/13538322.2020.1729309
|View full text |Cite
|
Sign up to set email alerts
|

The Bangladeshi higher education quality assurance framework: a pathway for transformation

Abstract: Bangladesh's approach to devising a Quality Assurance Framework in higher education has eventuated in less than a decade. The framework provides criteria within which universities must operate and encompasses internal self-assessment review and monitoring besides external quality assurance, with the intrinsic goal of operationalising national protocols for a qualification framework. Based on the author's reflection regarding a programme self-assessment exercise as part of internal quality assurance procedure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…Recently, the number of HEIs in Bangladesh has increased significantly (Rahnuma, 2020). Until 2020, the Government of Bangladesh approved 46 public and 105 private universities with approximately 1.18 million students and 31,755 faculty members (BANBEIS, 2020).…”
Section: Online Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the number of HEIs in Bangladesh has increased significantly (Rahnuma, 2020). Until 2020, the Government of Bangladesh approved 46 public and 105 private universities with approximately 1.18 million students and 31,755 faculty members (BANBEIS, 2020).…”
Section: Online Crisismentioning
confidence: 99%
“…In addition, Javed et al (2020) demonstrated that responsible leadership increases relational social capital, improves the social performance of organisations, and fosters community citizenship amongst public sector employees in emerging economies such as Pakistan. Rahnuma (2020) emphasised the role of academic leaders in ensuring quality assurance in Bangladeshi HEIs. Responsible leadership is critical in HEIs because the value-based leadership style focusses on employees, organisations and society (Haque et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Findings show the positive effects and impacts of human resource quality on the quality assurance system. Rahnuma (2020), interpreted educational quality assurance by effective implication of human resource quality in the higher secondary institutions of Bangladesh. For achieving these intrinsic goals and qualifications, human resource quality is an important measure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The stakeholders also engaged in the policy debate and several policies were formulated. In many cases, policies at the state, academic, and industry levels were influenced by these researches [11,12].…”
Section: Introductionmentioning
confidence: 99%